PDGF-D, a new protease-activated growth factor - LaRochelle, William J.; Jeffers, Michael; McDonald, William F.; Chillakuru, Rajeev A.; Giese, Neill A.; Lokker, Nathalie A.; Sullivan, Carol; Boldog, Ferenc L.; Yang, Meijia; Vernet, Corine; Burgess, Catherine E.; Fernandes, Elma; et al. (Nature cell biology, 2001)
Platelet-derived growth factor (PDGF) has been directly implicated in developmental and physiological processes 1 , 2 , 3 , 4 , 5 , as well as in human cancer, fibrotic diseases and arteriosclerosis 6 . The PDGF family currently consists of at least three gene products, PDGF-A, PDGF-B and PDGF-C, which selectively signal through two PDGF receptors (PDGFRs) to regulate diverse cellular functions. After two decades of searching, PDGF-A and B were the only ligands identified for PDGFRs. Recently, however, database mining has resulted in the discovery of a third member of the PDGF family, PDGF-C 7 , 8 , a functional analogue of PDGF-A that requires proteolytic activation. PDGF-A and PDGF-C selectively activate PDGFR-α 7 , 9 , 10 , whereas PDGF-B activates both PDGFR-α and PDGFR-β 9 , 11 . Here we identify and characterize a new member of the PDGF family, PDGF D, which also requires proteolytic activation. Recombinant, purified PDGF-D induces DNA synthesis and growth in cells expressing PDGFRs. In cells expressing individual PDGFRs, PDGF-D binds to and activates PDGFR-β but not PDGFR-α. However, in cells expressing both PDGFRs, PDGF-D activates both receptors. This indicates that PDGFR-α activation may result from PDGFR-α/β heterodimerization.